AN ANALYSIS OF RESTORATIVE JUSTICE PRINCIPLES APPLIED BY CIVIL SERVANT INVESTIGATORS (PPNS) IN HANDLING ANIMAL, FISH, AND PLANT QUARANTINE CRIMES UNDER LAW NUMBER 20 OF 2025 ON THE CRIMINAL PROCEDURE CODE - Yasin Arifin; Baharudin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the application of restorative justice principles by Civil Servant Investigators (PPNS) in handling animal, fish, and plant quarantine criminal offenses under Law Number 20 of 2025 concerning the Criminal Procedure Code, as well as the inhibiting factors to its implementation. The main issue is the inconsistency between the spirit of restorative justice and the characteristics of quarantine criminal offenses that position the state as the victim. The research employs normative juridical and empirical approaches using in-depth interviews with three informants at the Lampung Animal, Fish, and Plant Quarantine Center and literature study. The analysis applies S. Prajudi Atmosudirjo's Theory of Administrative Law, Aristotle's Theory of Justice, Satjipto Rahardjo's Progressive Law Theory, and Lawrence M. Friedman's Legal System Theory. The findings reveal that although Law Number 20 of 2025 has normatively opened space for the application of restorative justice, in practice it cannot be formally implemented due to three systemic obstacles: legal vacuum (rechtsvacuum) at three levels of regulation, structural weakness of PPNS institutions, and the dominance of repressive paradigms in the legal culture of authorities. The study concludes that the application of restorative justice possesses philosophical, juridical, and sociological legitimacy for development, but requires policy reformulation through the drafting of technical regulations, institutional strengthening, classification of violation risks, and development of a legal culture oriented toward substantive justice.